ICANN MECHANISMS: EXTRA REMEDIES EVALUATION - wahdani, Fahed A.fahed (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
At incorporation with World intellectual property organization, ICANN has created administrative mechanisms to solve contested domain names and other rights related to the use of trademarks in Cyberspace. In this context, this mechanism called UDRP was limited to general top-level domain names. At the early beginning of the world wide web, the conflicts were basically surrounded by domain names chains such as .com, .org, .net high trade value. On top of that, and because the increasing demand in the domain names industry was huge, ICANN seeks to pump new domain names chains into the market to encounter such an increasing demand over domain names. Accordingly, this step has increased the conflict while the UDRP mechanism was limited to solve the conflicts over top-level domain names. In this connection, ACANN had to find another mechanism to solve other conflict-related to the new gTLD. This article tries to shed light on these remedies and their effectiveness in solving such conflicts.
Keywords: RPMs, gTLDs, UDRP, Domain names, Trademark